Suara dalam Keheningan: Membaca Ulang Kisah Elia dalam 1 Raja-Raja 19:1-18 sebagai Dampak dari Trauma Psikologis - Huka, Elsami Castigliani (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
The story of Elijah in 1 Kings 19:1-18 is often understood as a narrative about disappointment and escape. This article aims to analyze the psychological trauma experienced by Elijah. The research focuses on Elijah's experiences following his battle against the prophets of Baal on Mount Carmel. Despite achieving victory, Elijah falls into depression and a desire to die due to the political threats from Jezebel. This article explores the parallels between Elijah's story and the characteristics of psychological trauma, such as feelings of threat, flashbacks, and avoidance. The journey from the wilderness to Mount Horeb brings Elijah to encounter God in a gentle voice and the whisper of a soft breeze, renewing his strength and giving him the confidence to continue his mission. This research employs qualitative methods with a literature review on psychological trauma and narrative text analysis to gain deeper understanding. Reading Elijah's story through the lens of psychological trauma offers several important lessons: first, trauma can be experienced by anyone, including those who seem strong; second, God is always present and provides healing for the wounded; and third, God's voice can come in silence and gentleness to guide us toward resilience.